African capitalism : a case study in Nigerian entrepreneurship - Nafziger, E. Wayne (Stanford, Calif. : Hoover Institution Press, 1977)
Nafziger's case study of the Nigerian footwear industry is a result of both hard and demanding field work that economists too seldom carry out and a thorough survey of the relevant literature on the Nigerian economy. While the book has its short comings it contributes solid information to our store of knowledge about the Nigeria economy and, by extension, about other African economies.
"Originated as a doctoral dissertation at the University of Illinois."
Includes index.
Bibliography: p. [265]-284.
rpm 08/11/2017
Loans
Keywords: Businesspeople; Entrepreneurship; Nigeria